Hubungan Antara Efikasi Diri dengan Motivasi Berprestasi Pada Mahasiswa Universitas X Yogyakarta - Ana Prihatin; Muslimah Zahro Romas; FX. Wahyu Widiantoro (Jurnal Psikologi, 2018)
Objective of this research was to understand the relationship between self- efficacy (independent variable) and achievement motivation (dependent variable) among university students. There were 60 students participated in this study, aged 18-21 years old, and full-time students. Two instruments were created in this study i.e. the self-efficacy scale and achievement motivation scale. The data collection was analyzed through the product moment correlation technique. This research revealed that there was a positive and significant correlation between the students’ self-efficacy and their achievement motivation (r = .683. p<.01). The self-efficacy variable was able to predict 46.6% of the achievement motivation. The rest was undetected under this research. Probably, the students’ employment situation should be considered, in spite of their status as the full-time students. Employment situation at this time is not only working at an organization, but also becoming an entrepreneur. At this time, it is very common among university students to be a startup entrepreneur. This working situation surely influences their achievement motivation.  Key words: Self-efficacy, Achievement Motivation, University Student.